Similitud de los parámetros de longissimus thoracis y el espesor de la grasa medidos mediante ecografía y análisis digital de imágenes - Ramos-Ramos, Cristino; Zaragoza-Vera, Claudia Virginia; Zaragoza-Vera, Maritza; Torres-Chable, Oswaldo; Barrientos-Medina, Roberto Carlos; Chay-Canul, Alfonso (Ecosistemas y Recursos Agropecuarios, 2024)
The aim of the present study was to evaluate the similarity of area (LTMAUS, cm2), depth (LTMDUS, cm) and width (LTMWUS, cm) of the longissimus thoracis muscle and fat thickness (SFTUS) measured by ultrasound and ImageJ software. Ultrasound measurements were performed on 36 male sheep 24 h prior to slaughter and immediately measured using electronic callipers with a resolution of 0.1 cm. Images were stored on a flash drive, opened on a computer and measured using ImageJ (LTMDDIA, LTMWDIA, LTMADIA and SFTDIA). There were no differences between ultrasound and ImageJ measurements (P = 0.3610) for Hotelling’s T2 test. Our results show that ImageJ software is a potential tool for in vivo measurement of longissimus thoracis parameters and fat thickness in hair sheep.